2020
DOI: 10.1245/s10434-020-09271-2
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Bioabsorbable Tissue Marker for Volume Replacement and Radiation Planning: A Multicenter Study of Surgical and Patient-Reported Outcomes for 818 Patients with Breast Cancer

Abstract: Background Accurate identification of the tumor bed after breast-conserving surgery (BCS) ensures appropriate radiation to the tumor bed while minimizing normal tissue exposure. The BioZorb® three-dimensional (3D) bioabsorbable tissue marker provides a reliable target for radiation therapy (RT) planning and follow-up evaluation while serving as a scaffold to maintain breast contour. Methods After informed consent, 818 patients (826 breasts) implanted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…There is currently a paucity of data related to the surgical complications secondary to use of a BioZorb. Reported complications seem to be minor and occur rarely 3,4 . However, our patient went on to complete post‐lumpectomy radiation for her DCIS, and nearly 9 months later presented with chronic symptoms of breast infection, pain, erythema, and ultimate erosion of the BioZorb through her skin 1 year after initial surgery.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…There is currently a paucity of data related to the surgical complications secondary to use of a BioZorb. Reported complications seem to be minor and occur rarely 3,4 . However, our patient went on to complete post‐lumpectomy radiation for her DCIS, and nearly 9 months later presented with chronic symptoms of breast infection, pain, erythema, and ultimate erosion of the BioZorb through her skin 1 year after initial surgery.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, there is improved visualization of the lumpectomy cavity on imaging due to the titanium clips. Studies have also noted positive patient‐reported long‐term cosmetic outcomes related to use of the BioZorb 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods to minimize uncertainties reported including the reference of preoperative CT, magnetic resonance imaging-based delineation, clip insertion, and tissue marker insertion. 16,37 However, no method has been established so far to achieve accurate cavity delineation.…”
Section: Discussionmentioning
confidence: 99%
“…Some centers are using this for patients who are receiving radiation boost to the tumor bed. Cosmetic outcomes over two years are reported by Kaufman in his study of 818 patients (54) to be good to excellent in over 87% of patients with adverse effects in 3.8% of patients (n=31). Our experience largely confirms what is reported (unpublished).…”
Section: Biozorbmentioning
confidence: 98%